Effect off oot and mouth disease vaccination on the reproductive capacity of the_ buffalo bulls - SINGH, R; VERMA, H K; KUMAR, S; MATHAROO, J S (The Indian Journal of Animal Reproduction, 2023)
The bulls which are used in Artificial Insemination should be maintained in disease free areas to prevent disease transmission.Vaccination is routinely done against bacterial and viral diseases. Vaccination is considered as a stress factor which affects the semenquality. Hence the present study was undertaken to observe the effect of FMD vaccination on the reproductive capacity of buffalobulls, which can alter the spermiograrn and ultimately the conception.
Keywords: FMD; Vaccination; buffalo; bull; reproduction